Oceans '97. MTS/IEEE Conference Proceedings
DOI: 10.1109/oceans.1997.624114
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic seabed classification and correlation analysis of sediment properties by QTC VIEW

Abstract: A 50 kHz echo sounder and a digital waveform acquisition and seabed classification system were used to record and process echoes from embayments near southeast Vancouver Island, Canada. Each echo was preprocessed and several statistical and spectral algorithms were used to extract its characteristic patterns. The patterns were grouped into four acoustic classes. Ground truth was available from each site allowing each cluster to be associated with a seabed type. The sediment properties and acoustic classificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 4 publications
0
10
0
1
Order By: Relevance
“…The results of this study suggest that particulate organic matter (POM) could be transported to the center of the bay head by the residual circulation driven by pumping velocity. Okada et al [2009] carried out a field experiment to measure moisture content of the sediment from 2003 to 2004 using Quester tangent [Co., QTC VIEW; Preston et al, 1999, Preston andCollins, 2000;Tsemahman and Collins, 1997]. These measurements were verified by comparison with sediment samples, and the field study demonstrated that sediment with a higher moisture content exists at the center of the bay head.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The results of this study suggest that particulate organic matter (POM) could be transported to the center of the bay head by the residual circulation driven by pumping velocity. Okada et al [2009] carried out a field experiment to measure moisture content of the sediment from 2003 to 2004 using Quester tangent [Co., QTC VIEW; Preston et al, 1999, Preston andCollins, 2000;Tsemahman and Collins, 1997]. These measurements were verified by comparison with sediment samples, and the field study demonstrated that sediment with a higher moisture content exists at the center of the bay head.…”
Section: Discussionmentioning
confidence: 94%
“…Okada et al . [] carried out a field experiment to measure moisture content of the sediment from 2003 to 2004 using Quester tangent [Co., QTC VIEW; Preston et al ., , Preston and Collins , ; Tsemahman and Collins , ]. These measurements were verified by comparison with sediment samples, and the field study demonstrated that sediment with a higher moisture content exists at the center of the bay head.…”
Section: Discussionmentioning
confidence: 99%
“…More recently acoustic ground-discrimination systems (AGDS) have been developed to detect the acoustic-reflectance properties of the seabed. Indeed, the nature of bottom echoes is influenced not only by basic sediment grainsize parameters, sediment sorting, microtopography, sediment density and porosity, but also by the presence, concentration and type of benthic fauna and flora (TSEMAHMAN & COLLINS, 1997;COLLINS & GALLOWAY, 1998;BORNHOLD et al, 1999;HAMILTON et al, 1999;KLOSER et al, 2001;ANDERSON et al, 2002;HUTIN et al, 2005). RoxAnnì (CHIVERS et al, 1990) and QTC VIEWì (COLLINS et al, 1996) are two widely used AGDSs to extract shape, energy or both features contained in the bottom acoustic signals.…”
Section: Single-beam Echo-sounders (Sbes)mentioning
confidence: 99%
“…In [2] a 50 Hz echosounder combined with a digital wave form acquisition and a seabed classification system were used to record and process echoes from embayments near southeast Vancouver Island, Canada; each echo was preprocessed and several statistical and spectral algorithms were used to extract its characteristic patterns. In [3] a review of the acoustic techniques for the identification, classification and mapping of benthic habitats is given, reporting the commonly employed acoustic devices and subsurface sensing techniques.…”
Section: Introductionmentioning
confidence: 99%